INFLUENCE OF DEMOGRAPHIC FACTORS ON THE SUCCESS OF FEMALE ENTREPRENEURS (CAHIERS MAGELLANES-NS, 2024)
The phenomenon of women empowerment through women entrepreneurship has emerged enormously in recent times. A large number of women entrepreneurs have been fascinated by new ventures to become economically and socially empowered. Several studies in the past focussed on the influence of demographic factors on the performance of women enterprises and women entrepreneurs. This study is focused on understanding the impact of demographic characteristics on the boutique industry in a select region of Jaipur. The study is based on a primary survey considering the identified demographic variables that impact the quantitative and qualitative performance of women entrepreneurs. The study finds that age, education and skill development, family support, and religion have a positive impact on the performance of boutique works taken up by women entrepreneurs.